A concept for process-oriented interdisciplinary tolerance management considering production-specific deviations - Heling, Björn; Oberleiter, Thomas; Rohrmoser, Andreas; Kiener, Christoph; Schleich, Benjamin; Hagenah, Hinnerk; Merklein, Marion; Willner, Kai; Wartzack, Sandro (Proceedings of the 22nd International Conference on Engineering Design (ICED19), 2019)

A methodology for the application of virtual evaluation methods within the design process of cold forged steel pinions - Rohrmoser, Andreas; Heling, Björn; Schleich, Benjamin; Kiener, Christoph; Hagenah, Hinnerk; Wartzack, Sandro; Merklein, Marion (Proceedings of the 22nd International Conference on Engineering Design (ICED19), 2019)

Basic numerical analysis of a “Samanta” based forward extrusion process - Kiener, Christoph; Andreas, Kolja; Merklein, Marion (Advanced Materials Research, 2016)
LFT Import::2019-07-29 (2181)

Berücksichtigung von produktionsspezifischen Abweichungen im interdisziplinären Toleranzmanagement - Heling, Björn; Oberleiter, Thomas; Rohrmoser, Andreas; Kiener, Christoph; Schleich, Benjamin; Hagenah, Hinnerk; Merklein, Marion; Willner, Kai; Wartzack, Sandro (Industriekolloquium der Forschergruppe FOR 2271, 2019)
LFT Import::2019-08-05 (2353)

Einsatz numerischer Analysetools bei der Auslegung und Herstellung kaltfließgepresster Stahlzahnräder - Rohrmoser, Andreas; Kiener, Christoph; Hagenah, Hinnerk; Merklein, Marion (Konstruktion, 2019)
In the drivetrain and transmission technology gears are used in large quantities, which is why an efficient and sustainable production is gaining importance. At the same time the application of new material combinations leads to a demand for adjustable component properties in order to positively influence the operational behavior. Cold forging provides the potential of manufacturing geared components with beneficial mechanical and geometrical properties in a highly productive process. However the industrial application of cold forging faces challenges regarding limited tool life and the achievable gear quality. To face these challenges the development of targeted approaches within the component and process design is necessary. In this context the application of numerical analyses offers a promising approach, which enables the investigation of the resulting operational behavior of the forming tool and gear.
LFT Import::2019-07-29 (2372)

Gezielte Beeinflussung der einsatzrelevanten Bauteileigenschaften kaltfließgepresster Zahnräder - Rohrmoser, Andreas; Kiener, Christoph; Schubert, Dirk W.; Hagenah, Hinnerk; Drummer, Dietmar; Merklein, Marion (Konstruktion, 2019)
LFT Import::2019-07-29 (2385)

Influence of tribological conditions on application relevant component properties of cold forged gears - Rohrmoser, Andreas; Kiener, Christoph; Hagenah, Hinnerk; Merklein, Marion (Production Engineering, 2019)

Influence of tribological conditions on cold forging of gears - Kiener, Christoph; Neher, R.; Merklein, Marion (Production Engineering, 2018)
Gears are integral and vital machine elements in the field of drive and transmission technology. With regard to economic and ecological aspects, cold forging represents a promising approach compared to conventional cutting processes for producing highly-loadable gears. A possible extrusion process for manufacturing helical gears is the so-called “Samanta”-process. In comparison to conventional extrusion processes, an additional ejector system is avoidable. Thus, in particular for helical gears, a negative impact on the gear quality by the ejector operation is prevented. Furthermore, the process chain during the component production cycle is shortened which leads to a more efficient production. The achievable gear accuracy as well as insufficient tool life are major challenges while establishing the “Samanta”-process in industry. To enable an industrial application, basic process understanding as well as knowledge about the influences on the process results is required. For influencing component and process properties within cold forging, approaches from the tribological system can be generally used. The aim of this study is to analyze the influence of the friction conditions on selected component and process properties within cold forging of gears by the “Samanta”-process. For adjusting the occurring friction, various lubrication systems were applied, which have been qualified using a double cup extrusion test (DCE-test). The results reveal that the lubrication system determines the friction conditions during forming. Within cold forging of helical gears by the “Samanta”-process, the friction influences the resulting strain hardening of the components and the required maximum forming force as well as the energy amount.
LFT Import::2019-07-29 (2285)
Keywords: Cold forging; Friction; Gears; Tool technology

Influence of tribological conditions on cold forging processes - Kiener, Christoph; Dohmstreich, J.; Andreas, Kolja; Merklein, Marion (Proceedings THE"A" Coatings, 2017)
LFT Import::2019-08-07 (2262)

Investigations on Residual Stress Generation in Extruded Steel Components - Jobst, Andreas; Kiener, Christoph; Merklein, Marion (9th Congress of the German Academic Association for Production Technology (WGP), 2019)
During the forming of components, inhomogeneous stress conditions lead to residual stresses, which influence the operating behaviour of the manufactured part. Compressive residual stresses generally have a positive effect, while tensile residual stresses reduce the fatigue strength and facilitate crack initiation. Full forward extrusion has been established as an industrial manufacturing technique, where cylindrical billets are formed in the die and ejected in opposite direction. In order to influence the residual stresses state, it is essential to know about its formation. A basic understanding is created by separate investigation of the forming and the ejection step. In the context of this paper, singlephase ferritic stainless steel X6Cr17 and ferritic-austenitic duplex steel X2CrNi- MoN22-5-3 are used. The quantification of the residual stresses states is carried out by X-ray diffractometry, for which a measurement method for duplex steel is validated. The influence of forming and ejection is determined separately by manufacturing components with and without an ejection operation.<br
Keywords: Residual Stress; Forward Extrusion; Stainless Steel

Investigations on residual stress generation in full-forward-extrusion - Landkammer, Philipp; Jobst, Andreas; Kiener, Christoph; Steinmann, Paul; Merklein, Marion (Production Engineering, 2019)
Within cold-forming processes, the influence of forming induced residual stresses is a critical issue regarding the life-time behaviour of the formed components. However, a targeted use of forming-induced residual stresses is also capable to improve the components properties. The rotation-symmetrical full-forward extrusion is used as a reference process to investigate the generation of residual stresses within manufacturing. A novel and generally applicable computational evaluation procedure is introduced, which achieves to compute and visualize the evolution of the residual stress state during the entire forming operation. Simulative results are compared with their experimental counterparts. The near-surface residual stresses in the formed component are evaluated in axial and tangential direction by X-ray diffraction. Indentation tests are used to determine the micro-hardness inside the components and optical instruments quantify geometrical difference
Keywords: Residual stresses· Full-forward-extrusion· Experimental validation· Advanced post processing

Kaltfließpressen von gerad- und schrägverzahnten Zahnrädern - Kiener, Christoph (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2020)
For gear manufacturing, cutting processes are used as standard due to the achievable manufacturing accuracy. Considering economic and ecological aspects, cold forging offers an alternative due to shorter production cycles and increased material efficiency. In addition, cold forged gears are more loadable in operation due to process-related hardening and a fiber-like microstructure. One variant of forward extrusion for the production of gears is the so-called Samanta-process. The decisive advantage of this process compared to conventional transverse and forward extrusion is that no ejection process is required. In addition to a positive effect on the achievable quantity output, an influence on the component accuracy is avoided during the ejection of the formed components out of the tool system. To apply the Samanta-process in industry, the achievable gearing quality and tool life have to be increased. Therefore, this work focuses on the determination of functional relationships between gear parameters and process variables in order to generate a fundamental process understanding for cold forging of gears in the Samanta-process. The research of methods for the beneficial influencing of the process result in order to derive practice-relevant recommendations for process design is also a key aspect of this wor

Mechanisms of residual stress generation in full-forward-extrusion - Landkammer, Philipp; Jobst, Andreas; Kiener, Christoph; Steinmann, Paul; Merklein, Marion (Production Engineering, 2019)
LFT Import::2019-07-29 (2366)

Numerical investigations on the influence of process parameters on the forming of gears in forward extrusion - Merklein, Marion; Kiener, Christoph; Zimmermann, Andrea (Applied Mechanics and Materials, 2015)
LFT Import::2019-07-29 (2128)

Researching of commonalities and differences in cold forging of spur and helical gears - Kiener, Christoph; Merklein, Marion (Production Engineering, 2019)
Modern automobiles are equipped with a large number of gear transmissions. In the powertrain, for example, they are used as multi-stage manual transmissions and in the interior for mirror and seat adjustment. Machining manufacturing processes—like gear hobbing and shaping—represent the state of the art in gear manufacturing due to high manufacturing accuracy and flexible machining possibilities. With regard to economic, ecological and technical aspects, cold forging offers a promising production technology. In conventional transverse and forward extrusion processes, the ejection process is a challenge due to high forces and a negative influence on the gearing accuracy. One variant of forward extrusion is the so-called “Samanta” process, whereby an additional ejection step is avoidable by sequential forming of the gears. For the establishment of this process in industry, the increase of the achievable gearing accuracy and the achievable tool life is of major relevance. Thus, a deeper process understanding as well as knowledge about the influences on the process results is beneficial. In this context, the aim of this research work is to produce spur and helical gears by the “Samanta”-process. In addition to the resulting component properties, the characteristics of the process are determined. On this basis, commonalities and differences in cold forging of spur and helical gears are investigated to gain a principle process understanding. These findings are also used to derive possible approaches for improving component and process properties in future research work. The results reveal that cold forging of spur and helical gears by the “Samanta”-process results in characteristic properties and specific challenges within the gear types. Furthermore, a geometric adaptation in the gearing area of the used die promises enormous potential for a positive influence on the process results for both types of gearing.
CRIS-Team Scopus Importer:2019-05-24
Keywords: Cold forging; Gears; Tool

Research of Adapted Tool Design in Cold Forging of Gears - Kiener, Christoph; Merklein, Marion (International Journal of Material Forming, 2019)
LFT Import::2019-07-29 (2383)

Smart FE-based tool design in cold forging - Andreas, Kolja; Kiener, Christoph; Engel, Ulf; Merklein, Marion (Advanced Materials Research, 2014)
In cold forging, the forming tool takes a key role. The present study focuses on the FE based analysis of different die sided leverages on the stress state in and the elastic behaviour of the forming tool. The results reveal a great influence of the workpiece material and the tool layout on the outcome of the forming process and the corresponding tool stresses.
LFT Import::2019-07-29 (2046)
Keywords: Cold forging; Design optimization; Tool

Targeted influencing of the mission-relevant component properties of cold-forged gearwheels - Rohrmoser, Andreas; Kiener, Christoph; Schubert, Dominik; Hagenah, Hinnerk; Drummer, Dietmar; Merklein, Marion (Konstruktion, 2019)
Cold forging offers the potential to produce ready-to-use gears in a process suitable for series production. In material pairing with a plastic gearwheel, the component properties of the steel gearwheel have a decisive effect on the wear behaviour and service life of the pairing. This results in requirements for the component properties that must be taken into account when designing the cold forging process. In the context of this article, the improvement of the resulting running-in behaviour of a steel-polyamide gear pairing by targeted measures within the design of the cold forging process of the steel pinion is investigated.
CRIS-Team Scopus Importer:2021-04-20

Untersuchung des Einsatzverhaltens kaltfließgepresster Zahnräder - Rohrmoser, Andreas; Kiener, Christoph; Hagenah, Hinnerk; Merklein, Marion (34. Jahrestreffen der Kaltmassivumformer, 2019)

Virtuelle Analysetools – Eine smarte Methode zur effizienten Erforschung von Kaltfließpressprozessen - Kiener, Christoph; Merklein, Marion (Konstruktion, 2017)
Gears are integral and vital machine elements in the field of drive and transmission technology. With regard to economic and ecological aspects, cold forging represents a promising approach compared to conventional cutting processes for producing highly-loadable gears. The achievable gear accuracy as well as an insufficient tool life is one major challenge during establishing cold forging processes in industry. Thus, the use of numerical analysis tools offers a great potential for an efficient and effective process research.
LFT Import::2019-07-29 (2263)